Penerapan Metode Full Time Equivalent (FTE) dalam Analisis Workload untuk Efisiensi Sumber Daya Manusia di Departemen Procurement PT. ABC - Syahfitri, Rini Widya; Mauliddina, Yasmin; Ranti, Gadih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. ABC faces a challenge of excessive workload in the Procurement Department, as indicated by a Full Time Equivalent (FTE) value of 2.4. This imbalance poses a risk of decreased productivity and work quality. This study aims to analyze employee workload using the FTE method, identify the factors contributing to workload disparity, and evaluate the effectiveness of this method in determining the optimal number of employees. The FTE method was applied by collecting data on available working time, effective working hours, allowances, and workload standards. The analysis revealed that the imbalance is driven by increased task volume, limited human resources, and job complexity. It is recommended to add one employee to each key position to distribute the workload more evenly